Is there a grade penalty for high school track and college degree mismatches? Evidence from the University of the Philippines - J. C. Punongbayan; Jefferson A. Arapoc (University of the Philippines, School of Economics (UPSE), 2025)
This study examines the consequences of college students pursuing degree programs that do not align with the tracks and strands they selected in senior high school. We utilize a unique dataset that links admissions and enrollment records from the University of the Philippines Diliman to investigate whether this mismatch affects students' academic performance. Using propensity score matching, we do not find evidence of a grade penalty for most degree programs. However, we estimate a significant grade penalty specifically for mismatch in science and engineering programs, where a strong background in the Science, Technology, Engineering, and Mathematics (STEM) strand is expected and in fact necessary for academic performance; i.e., students who did not come from the STEM strand tend to perform worse. These findings suggest that the choice of a SHS strand may maLer in some fields more than others, raising important questions about how SHS tracks are offered and how college admissions policies take high school backgrounds into account.
Keywords: I21; I23; I28; J24; 330; college performance; K to 12; mismatch; grade penalty; propensity score matching